Development Of Auditor Competency Standard Models - Miftahul Hidayat, Mohammad; Dedi Purwana; Agung Darmawan Buchdadi, (International Journal of Scientific Research and Management (IJSRM), 2022)
The government's internal audit is directed at building commitments in order to create good governance and clean government. The audit program aims to assess the credibility of the management's accountability report on organizational responsibilities. Auditors must be objective and selective in conducting assessments and must be able (competent) and earnest in carrying out their duties. To ensure the objectivity of the evaluation, the auditor must be independent of the auditee (the party being audited), both personally and organizationally, and to ensure his ability, the auditor must have broad and comprehensive knowledge in auditing. As well as an adequate understanding of the area being audited. With the support of good planning, standardized audit stages, and active supervision, it can show the accuracy of task execution.